2019
DOI: 10.1155/2019/5850629
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization of Long-Acting Contraceptive Methods and Associated Factors among Female Health Care Providers in East Gojjam Zone, Northwest Ethiopia, in 2018

Abstract: Introduction Sub-Saharan Africa, including Ethiopia, faces serious population and reproductive health challenges, indicated by a higher unmet need for family planning, especially for long-acting contraceptive methods, higher fertility, and population growth rates. The utilization of long-acting reversible contraceptive methods in Ethiopia and in particular in the study area is low. Objective This study aimed to assess the utilization of long-acting reversible contraceptive methods among female health care work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
31
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 8 publications
13
31
4
Order By: Relevance
“…Similarly, increased utilization of LARCs was observed among employed women compared to their counterparts. This finding is in line with studies conducted in different parts of Ethiopia [31][32][33] and Kenya. 26,34 This could have happened because employed women have increased access to information and frequent health institution contact to access the service LARCs methods.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, increased utilization of LARCs was observed among employed women compared to their counterparts. This finding is in line with studies conducted in different parts of Ethiopia [31][32][33] and Kenya. 26,34 This could have happened because employed women have increased access to information and frequent health institution contact to access the service LARCs methods.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is supported by findings from Rural Nepal, 42 Uzbekistan, 43 and western Kenya. 23 In contrast, the 2011 EDHS data 44 and other studies conducted in our country 19,45,46 contradict this finding.…”
contrasting
confidence: 60%
“…In this study, husband involvement was revealed important for long-acting contraceptive use to get the planned family size. This nding is consistent with the study conducted in Indonesia that husbands support the utilization of long-acting contraceptive methods [22,23]. This may be because decision making is made mostly by the husband.…”
Section: Discussionsupporting
confidence: 91%